Gender and morality in Anglo-American culture, 1650-1800 - Bloch, Ruth H., 1949- (University of California Press, 2003)
A collection of essays on the origins of Anglo-American conceptions of gender and morality. The volume illuminates the overarching theme by addressing a basic historical question: Why did the attitudes toward gender and family relations that we now consider traditional values emerge when they did?